DEVELOPMENT OF INTERACTIVE LEARNING MEDIA BASED ON GOOGLE SITES WEBSITES FOR SCHOOL SUBJECTS OF BUDDHISM AND MORALS FOR JUNIOR HIGH SCHOOL CLASS VIII DURING IN THE PANDEMIC - Listyo, Dwi; Sukodoyo, Sukodoyo; Waluyo, Waluyo (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2022)
This study aims to explain the process of creating a google sites website to produce an online learning media that will help BME learning activities at the junior high school level. This type of research is research and development with the ADDIE approach. Data collection techniques used are interviews and questionnaires. Data credibility was assessed by transferability, dependability, confirmability, and logical validity. Data analysis techniques used for qualitative data are reduction, presentation, and conclusion. Quantitative data were analyzed by descriptive percentage theory. The product validation from the material experts obtained a feasibility percentage of 91.1% and from the website, the media expert obtained a feasibility percentage of 71.8%. The results of the user trial, namely the BME teachers and five Buddhist class VIII students also gave good responses to the product developed. The BME teachers conveyed that the learning media products based on the google sites were very effective. Some students also gave positive responses, that this learning media is quite interesting and more interactive.